Contact erosion initiated by clay dispersion beneath pavement layers. Issue 2 (4th March 2022) - Premkumar, S.; Piratheepan, J.; Rajeev, P.
ABSTRACT: Dispersive failures have been reported throughout the world in the recent past. Soils, in which they occur, are vulnerable to erosion even in quiet water. The initiation of dispersive failure below the pavement layers would progress without any sign and the consequences would be more severe than other types of pavement failure. This paper describes a theoretical development of an analytical model to quantify the mass of particle loss due to dispersion failure below the pavement layers and the associated transport and deposition of the detached particles. The analytical model is validated using the experimental results for four different materials with dispersive characteristics. The model calculations are compared with the experimental results and a close correlation is found between the model-calculated and experimental results. The calculated total mass loss per unit area for the most dispersive soil is 1.90 g/cm 2, which is very close to the experimental result of 1.72 g/cm 2 . The study indicates that the mass loss in the first water contact is significantly greater than those in the subsequent cycles for all the materials in the analytical and experimental results. Also, the calculated total mass loss is very close to the experimental results.